Millennials and the use of social networking sites as a job searching tool - Zarina Denan; Zarina Abdul Munir; Nurul Hazzira Fadzil; Kardina Kamaruddin; Mohd Redhuan Dzulkifli (Bulletin of Electrical Engineering and Informatics, 2020)
This research is conducted to examine the factors that influence the behavioural intention of millienials in using SNS when seeking for a job. The data was collected from respondents who are from the generation Y demographic and actively looking for jobs. The respondents must possess some experience in using SNS when job hunting. The data was then gathered and analyzed using partial least square (PLS) which encompasses the measurement and structural models of the study. The findings revealed that three of the constructs as applied in TAM are statistically significant to behavioural intention. The three factors that influenced the job seekers’ intention to use SNSs as a job search tool are; perceived usefulness, perceived ease of use and privacy concerns. All these factors are elements which contribute to and have a significant relationship with job seekers’ intention to use SNSs, as verified using PLS data analysis. The recruiters or employers who intend to adopt SNSs in the recruitment process are advised to design the recruitment plan regarding the utilization of SNSs to be more convenient and user-friendly. This study provides insight and knowledge regarding the impact of technology in online job application and hiring processes.